Genomic and evolutionary perspectives on bacteriophage ΦAfa-NA1 targeting MDR Gram-negative bacteria in diabetic ulcer - ERLIA NARULITA; DHIVA AULIA WINDA UTAMI; LAILI IZZATURROHMAH; HALIZA INAYAH ARRACHMI; RISKA AYU FEBRIANTI; RAYYAN ZHAFIR LUDFILLAH; AGUNG HARIS WIDIANTO; HARDIAN SUSILO ADDY; BINAR RAHMA UTAMI; KUSWATI KUSWATI; KAMALIA FIKRI (Society for Indonesian Biodiversity, 2025)
Abstract. Narulita E, Utami DAW, Izzaturrohmah L, Arrachmi HI, Febrianti RA, Ludfillah RZ, Widianto AH, Addy HS, Utami BR, Kuswati, Fikri K. 2025. Genomic and evolutionary perspectives on bacteriophage ?Afa-NA1 targeting MDR Gram-negative bacteria in diabetic ulcer. Biodiversitas 26: 6014-6024. The rise of Multidrug-Resistant (MDR) bacterial infections poses a significant challenge in clinical settings, particularly for diabetic ulcer patients who are highly susceptible to persistent infections. This study reports the isolation, characterization, and genomic analysis of a novel lytic bacteriophage, ?Afa-NA1, specifically targeting MDR Gram-negative bacteria associated with diabetic ulcers in Indonesia. The bacteriophage was isolated from wound dressings and tested against four clinical isolates: Alcaligenes faecalis T17, Pseudomonas sp. FP1911, and the Gram-positive control Streptomyces violaceoruber S21. ?Afa-NA1 exhibited strong lytic activity against three Gram-negative isolates but none against the Gram-positive control, confirming host specificity. ?Afa-NA1 produced clear plaques with an average diameter of 3.0±0.5 mm on Alcaligenes faecalis T17, indicative of its potent lytic activity. Stability tests showed the phage retained >90% infective titer after 24 hours at -20°C and 4°C, and exhibited robust stability across a wide pH range (pH 6 to 11). One-step growth analysis revealed a short latent period of 21.7±8.1 minutes and a burst size of 27.7±1.5 PFU per infected cell. Genomic analysis showed ?Afa-NA1 possesses a 78,105 bp double-stranded DNA genome with 45.8% G+C content encoding 83 predicted open reading frames. Comparative genomics and phylogenetic reconstruction confirmed its placement among T7-like Podoviruses, consistent with its obligate lytic lifecycle and genomic architecture. However, the potential for therapeutic application remains preliminary, as host range testing was conducted on a limited panel of single clinical isolates, and all assays were performed in vitro.